L’interférence du stigmate dans la prise en charge médicale. Le cas des mères célibataires - Amal Bousbaa (L’Année du Maghreb)
This article aims to study the interactions of single mothers in hospital structures, stopping mainly on the time of delivery. It is a question of reporting the articulations of stigma, related to pregnancy and reproduction outside marriage, with the objectives proclaimed by the State, on the one hand, and the practical practices of the nursing staff in single mothers, on the other hand. To provide some answers to these questions, we rely on the contributions of a qualitative survey conducted in Casablanca as part of a PhD thesis in Sociology. The methodological system is based on semi-structured interviews with single mothers, carers and community